Discovery of a gene cluster for the biosynthesis of novel cyclic peptide compound, KK-1, in Curvularia clavata - Yamaguchi, Shigenari; Fujioka, Tomonori; Yoshimi, Akira; Kumagai, Toshitaka; Umemura, Maiko; Abe, Keietsu; Machida, Masayuki; Kawai, Kiyoshi (Frontiers in Fungal Biology, 2023)
KK-1, a cyclic depsipeptide with 10 residues produced by a filamentous fungus Curvularia clavata BAUA-2787, is a promising pesticide active compound with high activity against many plant pathogens, especially Botrytis cinerea. As a first step toward the future mass production of KK-1, genome sequencing of C. clavata BAUA-2787 and transcriptome analysis were conducted, and a region of approximately 71 kb was found, containing 10 open reading frames, which were co-induced during KK-1 production, as a biosynthetic gene cluster. These include kk1B, which encodes nonribosomal peptide synthetase with a domain structure that is consistent with the structural features of KK-1, and kk1F, which encodes a transcription factor. To analyze the functions of these genes, a transformation system was developed for C. clavata, which enabled genetic engineering, including the overexpression and deletion of genes. The overexpression of kk1F increased the expression of the entire cluster genes and, consequently, improved KK-1 production, whereas its deletion decreased the expression of the entire cluster genes and almost eliminated KK-1 production, demonstrating that the protein encoded by kk1F regulates the expressions of the other nine cluster genes cooperatively as the pathway-specific transcription factor. Furthermore, the deletion of each cluster gene caused a reduction in KK-1 productivity, indicating that each gene is involved in KK-1 production. The genes kk1A, kk1D, kk1H, and kk1I, which showed a significant decrease in KK-1 productivity due to deletion, were presumed to be directly involved in KK-1 structure formation, including the biosynthesis of the constituent residues. kk1C, kk1E, kk1G, and kk1J, which maintained a certain level of KK-1 productivity despite deletion, were possibly involved in promoting or assisting KK-1 production, such as extracellular transportation and the removal of aberrant units incorporated into the peptide chain.